South Grand Boulevard:user orientation as a catalyst for resiliency - Ryan, Jonathan Michael (Kansas State University, 2011)
Contemporary design of the urban environment focuses increasingly upon the quality of space found within the public right-of-way. Landscape architects and urban planners are beginning to ask new questions that deviate from the conventional streetscape designs of the latter half of the 20th century. Under the mantra “complete the streets,” communities all across America are calling for a paradigm shift towards multimodal, pedestrian-scaled urban rights-of-way. At the same time, existing stormwater and combined sewer infrastructure is nearing the end of its productive lifespan in cities all across the country and world. The direct costs associated with repairing this infrastructure combined with the indirect costs of poor water quality and a greater frequency and intensity of flooding events downstream present a strong argument for developing new, innovative ideas about how to best design the stormwater infrastructure of tomorrow. The reintegration of ecological processes into the urban fabric will act as a catalyst for the appreciation of genius loci (spirit of the place) and user meaning while mitigating downstream flooding, increasing water quality, and extending the lifespan of existing stormwater infrastructure. By studying the hierarchical categorization of urban rights-of-way according to increased levels of user orientation, this research project aims to clearly articulate a new theoretical framework for expanding upon the current discourse surrounding “complete streets” and “green streets” theory. In the long-term, it is both economically and socially profitable for cities to use ecological processes to reclaim auto-oriented, urban rights-of-way as valuable public space for the health, safety, and welfare of all their users.
Keywords: stormwater infrastructure; urban right-of-way; user orientation; resiliency; ecological urbanism; placemaking; Landscape Architecture (0390)